Perancangan Aplikasi Manajemen Proyek Pada PT. Sintech Berkah Abadi Berbasis Web - Yuni Roza; Yonky Pernando; Raymond Erz Saragih; Kaharuddin Kaharuddin; Ihsan Verdian (J-INTECH ( Journal of Information and Technology), 2023)
Project management is the activity of organizing, leading, and controlling company resources to achieve desired goals. PT. Sintech Berkah Abadi greatly needs such a system to support and improve services for the satisfaction of both employees and customers in their company's project activities. As a company operating in the software provider industry in the global market, offering business solutions with advanced technology, they face various challenges in data processing. These challenges include data errors or losses occurring in various stages such as application creation, data processing, approval processes, and project reporting. Therefore, PT. Sintech Berkah Abadi requires a web-based project management system application. The data collection methods used in this research are observation, interviews, and literature review, while the analysis method used is SWOT. The implementation of this project management system application can provide a solution for the company, making work processes more effective and efficient.